SENSUS PENDUDUK 1990: BEBERAPA CATATAN TENTANG KEUNGGULAN DAN KELEMAHANNYA - S.G. Made Mamas (Populasi, 1992)
Compared with the previous other censuses, the 1990 Population Census, besides its special advantages, apparently still has several weaknesses. Some weaknesses which may emerge have actually been tried to be anticipated in the census plans, even though various constraints are still difficult to overcome. As observed in the report, one of the weaknesses concerns with age. The joint score index of the 1990 Population Census is muchbetter than that of the previous censuses, but this index it self is yet not sufficient. The close calculation of several population indicators which was done both directly and indirectly, and the comparison between the 1991 Demographic and Health Survey shows that the data qualities ofthe 1990Population Census are considered as moderately satisfactory.